Patterns of variation in the mountain blackeye (Chlorocharis emiliae) in selected mountaintops in Sabah and Sarawak, Malaysia - Dency Flenny, anak Ausgustine Gawin (Universiti Malaysia Sarawak (UNIMAS), 2007)
Mountain blackeye (Chlorocharis emiliae), an endemic spesies to Borneo, is commonly found above 1,600 m above sea level. The known populations of this montane resident included: Mount Kinabalu and Mount Trus Madi in Sabah, Mount Mulu, Mount Murud, Tama Abo Range and Pueh Range in Sarawak, Maga mountains between Sabah and Sarawak border and Mount Nyiut, in Kalimantan, Indonesia. This spesies is divided into four sub-spesies; C. e. emiliae, C. e. trinitiae, C. e. fusciceps and C. e. moultoni. The division of mountain blackeye into four sub-spesies has triggered many questions such as how the spesies diverged morphologically, and when the diversification occur, and what are the factors that contribute to the sub-specific variation of that spesies. Probably, the differentiation could be due to the natural selection through adaptation processes and/ or neutral process via random genetic drift within or between populations.